Executive Function Improvement for Children with Autism Spectrum Disorder: A Comparative Study between Virtual Training and Physical Exercise Methods - Chaoxin Ji; Jun Yang; Lin Lin; Song Chen (MDPI AG, 2022)
This study evaluated and compared the effects of virtual training and physical exercise on the executive function of children with autism spectrum disorder (ASD). After screening, the final analysis of this study was conducted on three groups: a virtual training group (n = 34), a physical exercise group (n = 33), and a control group (n = 33). The experiment was conducted for nine weeks, of which the virtual training group and physical exercise group were conducted three times a week for one hour each time during the first six weeks, while the control group did not conduct virtual training nor physical exercise. During the last three weeks (week 6 to week 9), virtual training and physical exercise were not performed on all three groups. The three main components of executive function (working memory, inhibition, flexibility) of children with ASD were measured before the intervention, after the intervention (week 1 to week 6) and in the last three weeks (week 6 to week 9). The final results are that firstly, the executive function of the virtual training and physical exercise groups were simultaneously improved after the intervention. Secondly, after the intervention stopped, the executive function of the virtual training and physical exercise groups showed a downward trend. Therefore, the study concludes that the application of virtual training and physical exercise can effectively enhance the executive function of children with ASD.